Wills De Hass scrapbook - De Hass, Wills, 1818?-1910.; Morgan, Lewis Henry, 1818-1881.
Scrapbook containing correspondence, writings, a course syllabus, newspaper clippings, printed matter, photographs, and other material relating to De Hass's interest in archaeology, the history of Indians in North America, and the history of West Virginia. Correspondence (circa 90 items) and clippings pertain primarily to Indian mounds and relics, particularly in the upper Ohio River Valley. Tipped into House and House-Life of the American Aborigines by Lewis Henry Morgan, 1881. Index located near the end of the volume.
Physician and archaeologist.
Collection material in English.
Keywords: Archaeology; Burial -- Ohio River Valley; Earthworks (Archaeology) -- Ohio River Valley; Indians of North America -- Funeral customs and rites -- Ohio River Valley; Indians of North America -- History; Mounds -- Ohio River Valley; Indians of North America -- Ohio River Valley; Indians of North America -- Ohio River Valley -- Antiquities; Relics -- Ohio River Valley; West Virginia -- History; Archaeologists; Physicians